Pembentukan Jiwa Wirausaha Peserta Didik Melalui Pelatihan Kuliner di Madrasah Aliyah Berbasis Teori Belajar Sosial - Ririn Kurniawati; Decky Avrilianda (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2026)
An entrepreneurial spirit refers to attitudes, behaviors, and mindsets that reflect courage, creativity, independence, and the ability to manage risk to achieve business goals. This spirit is crucial to cultivate from an early age, particularly during adolescence, which is a crucial transitional phase in the formation of identity and mindset. Developing an entrepreneurial spirit is not an instant process; it must be instilled and developed systematically. Culinary training at Islamic Senior High Schools can serve a dual purpose: honing technical cooking skills while instilling entrepreneurial values such as innovation, risk-taking, business management, and product marketing. Bandura stated that people learn not only from direct experience but also by observing how others behave and how that behavior impacts them. This study develops students' entrepreneurial spirit through culinary training, particularly at the Madrasah Aliyah level, to hone their skills. The study used a qualitative approach with a case study to explore in-depth the process, experiences, and perceptions of MAM 02 Plus Skills students in developing an entrepreneurial spirit through culinary training based on social learning theory. The results of the study show that this need is not merely an academic demand, but rather a form of self-actualization for students who want to have independence after graduating from school, especially for students who do not continue their education to a higher level. This study confirms that the process of developing an entrepreneurial spirit in students at MAM 02 Plus Skills takes place through social interactions and contextual learning experiences. Bandura's social learning theory has proven to be a relevant foundation because students learn from their environment, imitate productive behavior, and are motivated by the tangible results they achieve.